COVID-19, infection prevention and control within acute inpatient mental health facilities: a new challenge requiring a new approach. (1st September 2020) - McLean, Lisa; Forrester, Louise
Mental Health inpatient units have a primary purpose of treating mental health problems, managing disturbance and promoting social contact and support networks. These factors can conflict with optimal infection prevention and control (IPC) measures; This commentary describes an IPC perspective of the challenges in managing the effects of the COVID-19 pandemic that are specific to acute mental health settings. It points out the main areas for IPC and mental health practice development; The need for a new paradigm in the relationship between IPC and mental health specialists is identified. Recent collaboration between mental health and IPC specialists in evaluating personal protective equipment (PPE) for use in restraint is outlined.